Abstractness and its Role in Optic Art - يازجي, احمد; حويجة, ليندا (Latakia University Journal -Engineering Sciences Series, 2021)
Optical art relies on the use of mathematical laws to create formative paintings that suggest the aesthetic values ​​of movement, stillness, depth, and the delusion of the emergence of a painting on a flat surface. Since the art of optical illusion is an evolution of abstract art, the goal of the research lies in revealing how important abstractness is in moving the art of visual illusion to an evolving trend, and making the spectator as a partner in the artwork based on the kinetic effect. The research reviews the history of optic art emergence and its technical characteristics, and the definition of abstract art and its features and the relationship between it and optical illusions, while addressing the most important pioneers of each art, And how the new liberal thought began to transcend the artist's traditional static view of plastic work and its involvement in technological development as a means of research, which in turn has given rise to new artistic styles such as the Anamorfices art and other arts as the artistic Grandiose perspective in photography.